Strategy for Development of Research and Service to The Community of Al Islam Lecturers - Ibrahim Ibrahim (PINISI Discretion Review, 2022)
The limited space for lecturers of Al Islam kemuhammadiyaan in self-development in increasing the Tri Dharma of Higher Education. The purpose of this study is how to develop research strategies and community service lecturers at Al Islam Kemuhammadiyaan, University of Muhammadiyah Mataram. the method used is through non-formal interviews with AIK lecturers and data analysis using SWOT. The analysis consists of internal and external factors. Decisions are taken from the results of the collaboration of internal and external factors. The results of this study indicate that the strategies for developing research and community service for AIK lecturers at the University of Muhammadiyah Mataram include: 1) Increasing writing, researching and serving skills, 2) Increasing cooperation with all parties, especially PTMA throughout Indonesia in supporting AIK values through research. and Collaborative PKM, 3) Have the initiative to compete and develop themselves, and 4) Need innovation and creation among AIK lecturers. There needs to be a self-development strategy through self-initiative, so as to be able to compete globally.